COMPARISON OF VALUE ADDED OF WHITE PEPPER AND BLACK PEPPER IN EAST LUWU - A N Tenriawaru; M. Salam; M H Jamil; Nadila Anindita; Rustam Abd Rauf (AGROLAND The Agricultural Sciences Journal (e-Journal), 2022)
Pepper is the main commodity South Sulawesi and is the main source of income for farmers. Potential that is owned, has the opportunity to increase product competitiveness in obtaining added value. The method used is a case study on the pepper business in South Sulawesi Province, Indonesia. Data were analyzed using value-added analysis using Hayami's value-added method. The results of the analysis show that the value added generated by processing pepper seeds into powdered white pepper is IDR 197,218/kg, which means that for every 1 kg of raw material for white pepper seeds will be added IDR 197,218/kg, while the value added of ground black pepper is IDR 202,474/kg, which means that for every 1 kg of black pepper seed raw material, an value added of Rp.202,474/kg will be generated. The resulting profitability for white pepper is 56.35 percent and for black pepper is 57.85 percent. This shows that the processing of peppercorns into powdered pepper can generate profits of 56.35 percent white pepper and 57.85 percent black pepper respectively. The policy to increase ground pepper production has contributed positively to improving the regional economy, with the value added of black pepper and white pepper above 55 percent.